Modifikasi Resep Brownis Untuk Makanan Selingan Penderita Diabetes Mellitus - Setyowati Setyowati (Poltekkes Kemenkes Yogyakarta, 2017)
Background: The nutritional therapy management of diabetes mellitus patient lies in the proper diet and food selection arrangement. There is an eating recomendation (3 times for main food and 3 times of snackfood) that needed to be noted. One of the snack food that been allowed is brownie, as baked product and cake category. Modification on brownie recipe are needed to improve quality of the food. Objective: To understand a brownie recipe as snack food for diabetes mellitus patient based on physical quality, organoleptic quality, nutritional value and fiber content. Methods: The type of this research is an artificial experiment. The variables were modified brownie recipes; physical quality; organoleptic quality to colour, flavor, aroma, and texture; nutritional value, and fiber content. The subject of the study are 36 people with diabetes and 17 expert panelists. The object of this research is 3 kinds of brownie (red bean brownie, green bean brownie and peanut brownie). This research is conducted at Poltekkes Kemenkes Yogyakarta and Prolanis Organization in Puskemas Gamping 1 area, Sleman, Yogyakarta on February-September 2016. The data analysis of this research is done descriptively and analytically. Results: There is 3 brownie as modification results (green bean brownie, red bean brownie and peanut brownie). Those brownie have physical traits such as darker brown in colour, little bit sweet, have nutty flour aroma and little bit soft as a texture. Based on organoleptic quality, peanut brownie is the most preferred brownie. Based on analysis of chemical nutrition and fiber. Brownies tahat qualify the diet of people with diabetes mellitus is peanut brownie. Peanut brownie also been accepted by diabetes mellitus patient. Conclusion: Peanut brownie as modification results choosen as snack food alternatives for diabetes mellitus patient. Key words: Recipe, Brownie, Diabetes Mellitus